2021
DOI: 10.1002/lio2.676
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of severe dysphagia following radiotherapy for head and neck cancer

Abstract: Objective To investigate if severe dysphagia following radiotherapy for head and neck cancer (HNC) could be predicted by patient and tumor characteristics, feeding tube use, weight factors, jaw opening function, and saliva secretion. Methods Data was collected from 94 HNC patients 6 to 36 months post radiotherapy. Swallowing function was assessed by videofluroscopy (VFS). Severe dysphagia was defined by Penetration Aspiration Scale (PAS) as PAS≥5 or a total score ≤60 on the M. D. Anderson Dysphagia Inventory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Although the mechanism of this relationship is not well understood, other studies following radiotherapy for head and neck cancer have also demonstrated a correlation between higher BMI and decreased risk of severe dysphagia. 39 Finally, surgical factors such as free-flap reconstruction and NG tube dependence >3 weeks are predictive of future events of aspiration/penetration and may be early indications for more frequent SLP monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of this relationship is not well understood, other studies following radiotherapy for head and neck cancer have also demonstrated a correlation between higher BMI and decreased risk of severe dysphagia. 39 Finally, surgical factors such as free-flap reconstruction and NG tube dependence >3 weeks are predictive of future events of aspiration/penetration and may be early indications for more frequent SLP monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…A Likert 5-level scoring method was adopted; the responses “fully agree”, “agree”, “do not know”, “disagree”, and “completely disagree” were scored as 1, 2, 3, 4 or 5 points, respectively, and the total score was 20–100 points. A total score of less than 60 is defined as swallowing dysfuntion [ 23 ]. The higher the score, the better the patients rated their quality of life in terms of swallowing.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to acute mucositis, BMI < 22 was associated with late-stage dysphagia (Table 3). Overweight and increasing BMI predicted a lower risk of severe dysphagia after radiotherapy for head and neck cancer (19). Thus, swallowing training during/ after CCRT should be considered for patients with a low BMI to prevent post-CCRT dysphagia.…”
Section: Dysphagia Among Late Adverse Eventsmentioning
confidence: 99%